'Nothing new under the sun': Rethinking recycling in the past– Editorial. (24th May 2022) - Sainsbury, Victoria A.; Liu, Ruiliang
Abstract: Editorial for the Special Issue of Archaeometry 'Tackling Recycling in the Past'. The practice of recycling has undoubtedly become one of the most important strategies to build a long‐term sustainable society in the modern world. However, both the perception and practice of recycling can be traced back to prehistory through various archaeological records. Objects made of stone, jade, mortar, textiles, pottery and bones display evidence of physical reshaping and repair, as do objects of metal and glass. Metal and glass, moreover, are materials which can be melted and recast, freeing ancient people from the limitations of the physical form of the original object. Illustrating and understanding patterns of recycling and the underlying social organization can significantly advance our knowledge of ancient people, their economic, political and cultural motivations for recycling, as well as the broad interaction between the social and material world. Though the issue of recycling is not novel in the discussions and debates of the archaeological circle, new theoretical frameworks, methodologies and archaeometric data encourage us to revisit the topic in this special issue. In this editorial, we consider what recycling means in the past, and why these papers are vital.